Decision Support System for Determining the Right Fertilizer for Coffee Plants Using the AHP Method - Yusnanto, Tri; Fatkhurrochman, Fatkhurrochman; Muin, Muhammad Abdul (Institut Teknologi Bisnis AAS Indonesia, 2024)
Coffee is one of the leading commodities in the plantation subsector in Indonesia. Padangan Hamlet is a hamlet located in Kandangan District, Temanggung Regency, with the majority of the community as coffee farmers. However, over time, coffee productivity has decreased and a strategy is needed to increase coffee productivity. To improve the quality of good coffee, special knowledge is needed regarding fertilization of coffee plants. Determining the right fertilizer for coffee farmers is an important problem because it can affect the crop yield. In providing solutions related to this problem, this study developed a decision support system for determining the right fertilizer for coffee plants using the AHP method. The system was developed using the waterfall process model with PHP and MySQL programming languages based on the Codeigniter framework. The system was tested for functionality and validity. In addition, the system was also evaluated and a feasibility study was carried out on the system against 8 respondents consisting of members of the farmer group. The results showed that the percentage value was 81.852% which indicated that the system was categorized as very feasible.